Immunoreactivity and neutralization capacity of Philippine cobra antivenom against Naja philippinensis and Naja samarensis venoms. (18th September 2020) - Tan, Choo Hock; Palasuberniam, Praneetha; Blanco, Francis Bonn; Tan, Kae Yi
Abstract: Background: The Philippine cobra ( Naja philippinensis ) and Samar cobra ( Naja samarensis ) are two WHO Category 1 medically important venomous snakes in the Philippines. Philippine cobra antivenom (PCAV) is the only antivenom available in the country, but its neutralization capacity against the venoms of N. philippinensis and hetero-specific N. samarensis has not been reported. This knowledge gap greatly hinders the optimization of antivenom use in the region. Methods: This study examined the immunological binding and neutralization capacity of PCAV against the two cobra venoms using WHO-recommended protocols. Results: In mice, both venoms were highly neurotoxic and lethal with a median lethal dose of 0.18 and 0.20 µg/g, respectively. PCAV exhibited strong and comparable immunoreactivity toward the venoms, indicating conserved venom antigenicity between the two allopatric species. In in vivo assay, PCAV was only moderately effective in neutralizing the toxicity of both venoms. Its potency was even lower against the hetero-specific N. samarensis venom by approximately two-fold compared with its potency against N. philippinensis venom. Conclusion: The results indicated that PCAV could be used to treat N. samarensis envenomation but at a higher dose, which might increase the risk of hypersensitivity and worsen the shortage of antivenom supply in the field. Antivenom manufacturing should be improved by developing a low-dose, high-efficacy product against cobra envenomation.